A feasibility and acceptability study of liberate: an online, peer-supported, psychoeducational intervention for ultra processed food addiction - Bennett, Ellen; Lycett, Deborah; Whelan, Maxine; Bellamy, Erin L.; Banks, Sara; Patel, Riya (Frontiers in Psychiatry, 2025)
IntroductionUltra-processed food addiction (UPFA) is a growing popular topic in the research arena. There are calls for its classification for diagnosis as a substance use disorder and behavioural disorder. Although evidence for UPFA is increasing, effective interventions remain scarcely available. This is a feasibility ty -50and acceptability study of “Liberate,” an online, peer-supported psychoeducation intervention for adults self-identifying with UPFA.MethodsA single-group, pre- and post-mixed methods study with 6-month follow-up was used. Participants (n=86) attended a 6-week coach-led online programme which comprised educational sessions, peer-to-peer support, and a personalised abstinence or harm reduction approach to dietary changes. Quantitative data included UPFA symptom measurements (YFAS 2.0, CRAVED), mental wellbeing (WEMWBS), and anthropometrics (weight, kg, and body mass index [BMI]). Acceptability was assessed qualitatively using semi-structured interviews which were then analysed thematically using the Theoretical Framework of Acceptability.ResultsRecruitment and retention rates were acceptable. Statistically significant improvements were observed in UPFA symptoms (YFAS mean reduction: −3.4; 95% CI: −4.5, −2.3), CRAVED scores (−1.4; 95% CI: −1.8, −0.9), and mental wellbeing (5.4; 95% CI: 3.2, 7.6) from baseline, post-intervention, and sustained at 6-month follow-up. BMI and weight change also showed a statistically significant reduction, but this was clinically negligible. Thematic analysis revealed high acceptability, with participants reporting greater self-awareness, reduced impulsive eating and eating behaviours, and increased confidence in managing UPFA symptoms. They found Liberate to be a psychologically safe and non-judgemental space, becoming aware that it was “not my fault,” and developing hope of a future beyond the intervention. Peer support and education on the effects of addiction on the brain were reported as being particularly beneficial. They expressed a desire that healthcare professionals would refer to Liberate.ConclusionThis study finds “Liberate” an online UPFA intervention, to be a feasible and acceptable intervention. Further investigation through a randomised controlled trial would be needed to establish causality, long-term effectiveness, and potential scalability.